Risking difference : identification, race, and community in contemporary fiction and feminism - Wyatt, Jean. (Albany : State University of New York Press, 2004)
"Risking Differences revisions the dynamics of multicultural feminist community by exploring the ways that identification creates misrecognitions and misunderstandings between individuals and within communities. Drawing on Lacanian psychoanalysis, Jean Wyatt argues not only that individual psychic processes of identification influence social dynamics, but also that social discourses of race, class, and culture shape individual identifications. In addition to examining fictional narratives by Margaret Atwood, Angela Carter, Sandra Cisneros, Toni Morrison, and others, Wyatt also looks at nonfictional accounts of cross-race relations by white feminists and feminists of color."--Jacket
Part I. Totalizing identifications -- the politics of envy in Academic feminist communities and in Margaret Atwood's The Robber Bride -- I want you to be me: parent-child identification in D.H. Lawrence's The Rainbow and Carolyn Kay Steedman's Landscape for a Good Woman -- Identification with the Trauma of Others: Slavery, Collective Trauma, and the difficulties of representatoon of Toni Morrison 's Beloved. Part II Structures of identtification in the Visual Field -- Race and idealization in Toni Morrison's Tar Baby and in White Feminist Cross-Race Fantasies -- Luring the gaze: desire and interpellation in Sandra Cisneros's "Woman hollering Creek, ", Anne Tyler's Saint Maybe, Angela Carter's The magic Toyshop, and Margaret Drabble's Jerusalem the Golden -- Disidentification and border negotiations of Gender in Sandra Cisneros's Woman Hollering Creeik -- Part III Heteropathic identifications -- Toward Cross-Race Dialogue: Cherrie Moraga, Gloria An zaldua, and the psychoanalytic politics of community.
Includes bibliographical references (pages 251-273) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: American fiction -- Women authors -- History and criticism; Feminism and literature -- United States -- History -- 20th century; Women and literature -- United States -- History -- 20th century; American fiction -- African American authors -- History and criticism; African American women -- Intellectual life; Psychoanalysis and feminism -- United States; Psychoanalysis and culture -- United States; Identification (Psychology) in literature; Multiculturalism in literature; Group identity in literature; Communities in literature; Race in literature; American fiction -- History and criticism; Feminism and literature -- United States -- 20th century -- History and criticism; American literature -- Women authors -- History and criticism; Roman américain -- Histoire et critique; Littérature féministe -- États-Unis -- 20e siècle -- Histoire et critique; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Roman américain -- Auteurs noirs américains -- Histoire et critique; Noires américaines -- Vie intellectuelle; Psychanalyse et féminisme -- États-Unis.; Ethnopsychanalyse -- États-Unis.; Identification (Psychologie) dans la littérature.; Multiculturalisme dans la littérature.; Identité collective dans la littérature.; Communauté dans la littérature.; Race dans la littérature.; Écrits de femmes américains -- Histoire et critique; LITERARY CRITICISM -- American -- General; American literature -- Women authors; American fiction; African American women -- Intellectual life; American fiction -- African American authors; American fiction -- Women authors; Communities in literature; Feminism and literature; Group identity in literature; Identification (Psychology) in literature; Multiculturalism in literature; Psychoanalysis and culture; Psychoanalysis and feminism; Race in literature; Women and literature; United States; Ethnische Beziehungen; Frauenliteratur; USA; Schwärze; Letterkunde; Amerikaans; Vrouwelijke auteurs; Feminisme; Identificatie (psychologie); Sekseverschillen; Multiculturele samenlevingen; 1900-1999; History; Criticism, interpretation, etc